Exploring the Contribution of (Poly)phenols to the Dietary Exposome Using High Resolution Mass Spectrometry Untargeted Metabolomics. Issue 21 (25th February 2022) - Li, Yuan‐Yuan; Rushing, Blake; Schroder, Madison; Sumner, Susan; Kay, Colin D.
Abstract : Scope: This study presents a workflow to construct a Dietary Exposome Library (DEL) comprised of phytochemicals and their metabolites derived from host and gut microbiome metabolism for use in peak identification/annotation of untargeted metabolomics datasets. Methods and Results: An evidence mapping initiative established target analytes related to the consumption of phytochemical‐rich foods. Analytes were confirmed by ultra‐performance liquid chromatography–mass spectrometry (UPLC‐MS(n)) analysis of human biospecimens from dietary intervention studies of (poly)phenol‐rich diets. One hundred and sixty six verified compounds were subsequently analyzed on an untargeted metabolomics platform to acquire chromatographic and high‐resolution mass spectral data for construction of a DEL. The DEL facilitated identification/annotation of 123 metabolites associate with exposure to (poly)phenol enriched diets, which included aromatic ketones, benzoic acids, ellagic acids, caffeoylquinic acids, catecholamines, coumarins, hippuric acid, hydroxytoluenes, phenylamines, stilbenes, urolithins, valerolactones, and xanthonoids, in untargeted metabolomics datasets acquire from human plasma and urine reference materials. Conclusions: The DEL focusing on (poly)phenols and their metabolites of dietary exposure facilitated identification/annotation of ingested food components and their associated pathways in untargeted metabolomics datasets acquired from human biospecimens. The DEL continues to expand with the aim to provide evidence‐based data for dietary metabolites in exposome research and inform the development of dietary intervention strategies. Abstract : A workflow is presented to construct a Dietary Exposome Library (DEL) for untargeted metabolomics, using evidence mapping, targeted and untargeted high‐resolution mass spectrometry. Here, this study demonstrates the ability to identify dietary phytochemicals (polyphenols) and their metabolites derived from host and gut metabolism in human reference materials and untargeted metabolomics datasets.